Comparing institution-building in East Asia : power politics, governance, and critical junctures - Yoshimatsu, Hidetaka (London : Palgrave Macmillan, 2014)
Includes biographical references and index
Keywords: Institution-building -- East Asia; Regional planning -- East Asia; Regionalism -- East Asia